Peningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran STAD (Students Team Achievement Division) Berbantu Metode Demonstrasi Mata Pelajaran Fiqih Di MTs YPM 2 Sidoarjo - Alya Wardani; Suparno (Jurnal Pendidikan Agama Islam Miazhar, 2023)
Classroom action research was conducted to improve the Islamic religious learning aspects of fiqh in fardhu prayer material in class VII M1 at MTs YPM 2 Sidoarjo. And the problems that researchers want to find answers to are 1) How is the application of the STAD (Student Team Achievement Division) learning model assisted by the Demonstration Method in Fiqh Subjects Fardhu Prayer Material in Class VII MTs YPM 2 Sidoarjo? 2) What are the student learning outcomes after the implementation of the STAD (Student Team Achievement Division) learning model assisted by the Demonstration Method in Fiqh Subjects Fardhu Prayer Material in Class VII MTs YPM 2 Sidoarjo?. In this study, limitations were carried out in the fiqh subject matter of fardhu prayers and in class VII M1. Limitation of this problem due to research limitations in terms of time, effort, and ability. This research is a classroom action research conducted in collaboration between educators and researchers in improving learning outcomes in the realm of knowledge and skills of students in fardhu prayers using the STAD (Student Team Achievement Division) learning model assisted by the Demonstration Method. The results obtained were by applying the STAD (Student Team Achievement Division) learning model assisted by the Demonstration Method the results of students' knowledge increased very well, this can be seen from the results in the pre-cycle 32%, increased in cycle I to 76%, and in cycle I cycle II increased to 95%. The results obtained were by applying the STAD (Student Team Achievement Division) learning model assisted by the Demonstration Method the results of students' skills increased very well, this can be seen from the pre-cycle results of 45%, increased in cycle I to 63%, and in cycle II increased to 95%.